2009
DOI: 10.1111/j.1601-5037.2008.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in detectable opportunistic bacteria in the oral cavity of orthodontic patients

Abstract: The isolation frequencies of opportunistic bacteria and fungi increase during orthodontic treatment, suggesting the importance of paying special attention to oral hygiene in orthodontic patients to prevent periodontal disease and the aggravation of systemic disease in immunocompromised conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
1
27
1
2
Order By: Relevance
“…Kitada et al [38] compared patients with and without ligatures on the conventional brackets and found an increase in opportunistic bacteria such as P. aeruginosa, associated with the development of periodontal disease and chronic recurrent infections, which is in disagreement with the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…Kitada et al [38] compared patients with and without ligatures on the conventional brackets and found an increase in opportunistic bacteria such as P. aeruginosa, associated with the development of periodontal disease and chronic recurrent infections, which is in disagreement with the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…Se observó un incremento significativo de 15,0 a 46,7% de niños portadores de especies de Candida desde el inicio y a seis meses de iniciado el tratamiento ortodóntico, hallazgo similar a lo reportado por otros autores 9,15,30,31 . El presente trabajo, presenta evidencias significativas que la instalación de aparatología ortodóntica puede predisponer a la colonización por especies de Candida, probablemente, debido a la interferencia que tienen en un adecuado cepillado y limpieza de la cavidad oral, como previamente se ha reportado 15,32,33 . La inadecuada limpieza bucal favorece la acumulación de placa dento-bacteriana debido a la presencia de microorganismos orales que influyen en cambios en la microbiota oral 8,15,34 .…”
Section: Discussionunclassified
“…Kitada et al (18) found that the frequency of opportunistic bacteria and fungi in the oral cavity of orthodontic patients was higher than in those who did not receive orthodontic treatment. Opportunistic bacteria and fungi are frequently found at higher frequencies in patients with immunodeficiency disorders and the elderly, and the appliances used in orthodontic treatment may cause an oral environment where opportunistic organisms can develop and live.…”
Section: Discussionmentioning
confidence: 99%
“…If the immune system is weakened by the orthodontic appliance, special precautions should be taken to prevent diseases that may arise due to the increase in opportunistic bacteria and fungi. Researchers recommend that orthodontic appliances should not be used in immunocompromised individuals (18). Naranjo et al (20) stated that brackets affect plaque accumulation and colonization by superinfected bacteria, leading to more inflammation in the gingival tissues.…”
Section: Discussionmentioning
confidence: 99%